The Microbiome and the Brain - Perlmutter, David, 1954- (Boca Raton, FL : CRC Press, 2020)
Brain related disorders are among the most challenging health issues of our time. The development of effective therapeutic and preventive strategies for these disorders relies on a comprehensive understanding of the underlying causative mechanisms. And, until recently, these mechanisms have remained somewhat elusive. The newly discovered pivotal role of the intestinal microbiome in brain health, functionality, and resistance to disease is revolutionizing neuroscience. The Microbiome and the Brain, through the contributions of some of the most forward thinking researchers and clinicians in the field, comprehensively reveals the leading edge of our understanding of the fundamental role of gut microbes and their metabolites in a wide array of seemingly diverse brain issues including Alzheimer's disease, autism, multiple sclerosis, and mood disorders. In addition, mechanisms defining these relationships are explored along with a presentation of the state-of-the-art as it relates to interpretation of relevant laboratory assessments. Finally, novel therapeutic opportunities, derived from this exciting science are presented. Readers will learn: The highly validated relationship between alterations of gut microbes and their metabolites, and risk for Alzheimer's disease. The important link between autism and intestinal dysbiosis. Appropriate interpretation of available laboratory assessments of the intestinal microbiome. The potential role of fecal microbial transplant in neurological diseases. The influence of diet and other lifestyle choices on the microbiome as it relates to brain health and functionality.
Potential Role of Nutrition in the Microbiota-to-Brain Communication in ASDConclusions and Future Directions; References; Chapter 6: Alzheimer's Disease, the Microbiome, and 21st Century Medicine; Looking Forward; References; Chapter 7: Microbial Involvement in Alzheimer's Disease; Introduction: AD and Human Microbiome; Gut Microbiota and Alzheimer's; Impaired Microbiota and Alzheimer's; Human microbiome and risk factors of AD; Targeting Gut Microbiota for AD Interventions; Future Directions; Conclusions; References; Chapter 8: The Role of the Microbiome in Mood; INTRODUCTION
Description based upon print version of record.
The Gut and its Microbiota
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Alternative Medicine; MEDICAL / Neurology; MEDICAL / Nutrition; Brain -- Microbiology; Human body -- Microbiology